Vikings : Valhalla. Season one [videorecording (DVD)] - Stuart, Jeb (MGM, 2024)
Chronicles the adventures of some of the most famous Vikings who ever lived: the legendary Leif Eriksson, his headstrong sister Freydis Eriksdotter, and the ambitious prince Harald Sigurdsson. As tensions between the Vikings and the English royals reach a breaking point, these three Vikings begin an epic journey that will take them across oceans and through battlefields, as they fight for survival and glory!